Effects of orthopedic treatment using temporomandibular joint balancing appliance (TBA) at improving the symptoms of tic/Tourette syndrome: case report - O Sang Kwon; So Min Lee; Kwang-Ho Choi; Young Jun Lee; Jee Yeon Jung (Integrative Medicine Research)
Tic disorder is characterized as sudden, non-rhythmic, involuntary and repetitive movement or vocalization, and its onset occurs mainly in childhood or adolescence. The development of medication has been limited because of a lack of understanding of tic mechanisms, and behavioral treatment is recommended as a first-line treatment. In this case report, we observed three cases in which tic disorder or Tourette syndrome was treated with intraoral orthopedic treatment (FCST) combined with acupuncture and an herbal formula and was assessed using the Yale Global Tic Severity Scale (YGTSS), a visual analog scale (VAS) and video analysis. The symptoms were reduced in 30 days and remained at the reduced level until 240 or 300 days after the first day of treatment. Most of the symptoms were disappeared after 240–300 days. Therefore, we could conclude that orthopedic treatment combined with Korean medicine may be applied for tic disorder in accordance with the efficacy and low adverse event rate, and we also suggests a large-scale clinical report to provide concrete evidence before the global application. Keywords: Tic disorder, Tourette syndrome, orthopedic treatment, Functional cerebrospinal technic (FCST)